Mineral precipitation and geometry alteration in porous structures: how to upscale variations in permeability–porosity relationship? - Mohammad Masoudi; Mohammad Nooraiepour; Deng, Hang; Helge Hellevang (Energy & Fuels, 2024)
Porous materials in natural and engineered environments are subject to morphological changes resulting from interacting chemical and physical processes. The intricate nature of these coupled processes, occurring at various temporal and spatial scales, poses challenges in predicting alterations in porosity and permeability. Delineating the controls of mineral precipitation reactions is particularly challenging because it requires the implementation of nucleation criteria and growth mechanisms. By conducting pore-scale simulations, we investigated the impact of the amount and stochastic distribution of crystallites, controlled by nucleation, on pore geometry and permeability in two-dimensional porous structures. The observed relationships between porosity and permeability exhibit characteristics that differ from the ones that are typically applied in dissolving porous media because of the clogging effect. Additionally, we propose a stochastic framework that upscales the coevolution of permeability and porosity across length scales. This framework enables the upscaling of clogging behavior to continuum-scale simulations based on statistical probability distributions of permeability–porosity variations.